Cambridge dictionary of American english - Landau, Sidney I. (Cambridge University Press, 2000)
The best American English learner's dictionary is better than ever, with new words and new features. Based on the world's largest corpus of American English, the book and CD include up-to-date vocabulary, easy-to-understand definitions, helpful usage notes, and examples that show how English is really used.